2017
DOI: 10.21577/0100-4042.20170152
|View full text |Cite
|
Sign up to set email alerts
|

MORE ACTIVE AND SULFUR RESISTANT BIMETALLIC Pd-NI CATALYSTS

Abstract: The influence of the kind of metal precursor and the sequence of impregnation on the properties of Pd-Ni catalysts was evaluated during the test reaction of selective hydrogenation of styrene to ethylbenzene by means of physicochemical characterization. The focus was put on the final hydrogenating activity and the resistance to deactivation by sulfided compounds (thiophene). The used techniques of characterization were ICP, XPS, XDR, TPR, CO chemisorption and TEM. XPS results indicated the presence of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Except for the bimetallic 1%Ni-4%Pd catalyst, both metallic and oxidized states of Ni co-exist in all catalysts, with the broad and complex envelop showing a contribution at 855.7 eV corresponding to Ni in oxidized states that can be associated to Ni strongly interacting with the alumina support (aluminate) and/or to surface oxidized Ni, and another one at ca. 851.7 eV assigned to metallic Ni [39,40]. The 4%Ni monometallic sample was suggested to be more prone to surface oxidation than the catalyst with a lower loading, as evidenced by the highest intensity of the oxidized nickel contribution vs. the metallic one.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Except for the bimetallic 1%Ni-4%Pd catalyst, both metallic and oxidized states of Ni co-exist in all catalysts, with the broad and complex envelop showing a contribution at 855.7 eV corresponding to Ni in oxidized states that can be associated to Ni strongly interacting with the alumina support (aluminate) and/or to surface oxidized Ni, and another one at ca. 851.7 eV assigned to metallic Ni [39,40]. The 4%Ni monometallic sample was suggested to be more prone to surface oxidation than the catalyst with a lower loading, as evidenced by the highest intensity of the oxidized nickel contribution vs. the metallic one.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…In previous work, during the selective hydrogenation of styrene with different catalysts, it was found that chloride complex species (Pd x ⊐+ O y Cl z ) were present in the surface electronic and steric effects that improved the activity or the sulfur resistance. [36][37][38] However, the effects of the acidity, the residual chloride species, and the surface properties of the support on the catalytic performance have not been investigated in detail for the selective hydrogenation of medium/long chain alkynes, nor for the purification of alkene/ alkyne mixtures. In a previous work, low loaded Pd catalysts were prepared using chloride of tetraamminepalladium(II) [Pd(NH 3 ) 4 ] Cl 2 as a precursor solution.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of kinetic of the selective hydrogenation of pyrolysis gasoline were presented by Zhou et al (2007). The group has already been studying the activity and sulfur resistance of Pd-Ni, Pt-Ni and Pt-W bimetallic catalysts, prepared by successive impregnations, in the selective hydrogenation of styrene to ethylbenzene (Betti et al 2012a(Betti et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the publications deal with catalytic evaluations of bimetallic catalysts prepared by successive impregnations, in this way one metal is more supericial and the other remains covered (Alonso et al 2012;Gaspar et al 2008;Betti et al 2018). To our knowledge there are few studies using coimpregnated catalysts, where both metals are supericially exposed, so it would be interesting to characterize the active species, study the activity, selectivity and their sulfur resistance especially during the hydrogenation of styrene.…”
Section: Introductionmentioning
confidence: 99%